Pengaruh Metode Mnemonik terhadap Daya Ingat Siswa Kelas IV pada Mata Pelajaran IPAS di SDN 15 Cakaranegara - Mutiara Alisa; Setiani Novitasari; Fitri Puji Astria (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of the mnemonic method on the memory of fourth-grade students in the IPAS subject at SDN 15 Cakranegara in the 2025/2026 Academic Year. This study employed a quantitative approach using a quasi-experimental method and a Nonequivalent Control Group Design. The population of this study consisted of all fourth-grade students at SDN 15 Cakranegara, with the sample consisting of Class IV A as the control class and Class IV B as the experimental class. Data were collected through tests and observation. The research instrument was a memory test administered in the form of a pretest and posttest. The experimental class received treatment using the mnemonic method with acrostic, visual, and storytelling techniques. The data were analyzed using normality, homogeneity, and hypothesis tests with an Independent Samples t-Test at a 5% significance level. The results showed that the mnemonic method had an effect on the memory of fourth-grade students in the IPAS subject. This was evidenced by the results of the Independent Samples t-Test, which obtained a significance value (Sig. 2-tailed) of 0.000 < 0.05. Therefore, H₀ was rejected and Hₐ was accepted. Based on these results, it can be concluded that the mnemonic method had an effect on the memory of fourth-grade students in the IPAS subject at SDN 15 Cakranegara.